Downtown Spokane images, 1930-1949 - Nunemaker, Carolyn Hage (National Color Graphics, 1997)
The author has deep Spokane roots reaching back to 1889, when her grandparents arrived as immigrants from Norway immediately after the Spokane Fire. She spent several years researching this book in order to capture the look and feel of downtown Spokane between 1930 and 1949, a period neglected by other historians.